2018
DOI: 10.1590/s1678-9946201860017
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and risk factors of Ascarididae and other geohelminths in the soil of Uberlandia, Minas Gerais, Brazil

Abstract: Among the geohelminths, parasites from the Ascarididae family have a significant role in the human and animal health. This research aims to determine the prevalence of Ascarididae species in the soil in different areas located in a city of Minas Gerais State, Brazil (South America). The study was developed in squares, parks, sports clubs, orchards and municipal children's schools. Samples of sand/soil/grass were collected from January to August 2014. The optical microscope screening was performed through forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 26 publications
(35 reference statements)
1
7
0
5
Order By: Relevance
“…We believe this is the reason why the presence of STH was negligible. The influence of soil type on the distribution of STH has been observed in other studies [41, 46, 47] and future studies in Argentina should evaluate this relationship.…”
Section: Discussionsupporting
confidence: 57%
“…We believe this is the reason why the presence of STH was negligible. The influence of soil type on the distribution of STH has been observed in other studies [41, 46, 47] and future studies in Argentina should evaluate this relationship.…”
Section: Discussionsupporting
confidence: 57%
“…Baermann technique detected five larvae and Hoffmann two larvae, concluding that Baermann technique (Ueno & Gonçalves, 1998) was more efficient for larval recovery, as shown in this presente work. Mota et al (2018) in their evaluation studies in samples from parks, schools and clubs in Uberlândia-MG, employing different techniques compared to this present study, reported eggs of Ancylostoma sp., 11.90% by Hoffmann technique and 4.76% by Ritchie; Ascarididae eggs identification 5.43% and 12.5% respectively; and Strongyloides larvae 19.7% and 21.3%, respectively.…”
Section: Resultsmentioning
confidence: 42%
“…Condições precárias de vida, moradia e saneamento básico, na maioria das vezes são determinantes na transmissão dessa doença. A infecção com sinais clínicos é mais recorrente em crianças (MOTA et al, 2018). O diagnóstico da ascaridíase é feito pela observação de ovos no exame coproparasitológico pelas técnicas de flutuação.…”
Section: Resultsunclassified